Are medical marijuana users different from recreational users? The view from primary care. (4th September 2015) - Roy‐Byrne, Peter; Maynard, Charles; Bumgardner, Kristin; Krupski, Antoinette; Dunn, Chris; West, Imara I.; Donovan, Dennis; Atkins, David C.; Ries, Richard
<x xml:space="preserve">Abstract</x> Background and Objectives Marijuana is currently approved for medical use in 23 states. Both clinicians and the lay public have questioned whether users of marijuana for medical purposes are different from users of marijuana for recreational purposes. This study examined similarities and differences in important clinical characteristics between users of medical marijuana and users of recreational marijuana. Methods The sample consisted of 868 adult primary care patients in Washington State, who reported use of medical marijuana (n = 131), recreational marijuana (n = 525), or drugs other than marijuana (n = 212). Retention was over 87% at 3‐, 6‐, 9‐, and 12‐month assessments. Results The majority of medical, psychiatric, substance use, and service utilization characteristic comparisons were not significant. However, medical marijuana users had significantly more medical problems, a significantly larger proportion reported >15 days medical problems in the past month, and significantly smaller proportions reported no pain and no mobility limitations (p < .001). Medical marijuana users also had significantly lower drug problem severity, lower alcohol problem severity, and significantly larger proportions reported using marijuana alone and concomitant opioid use only (p < .001). There was no significant difference between medical and recreational users in the percentage using marijuana with at least two additional substances (48% vs. 58%, respectively, p = .05). Conclusions and Scientific Significance Although our results suggest that there are few distinct differences between medical and recreational users of marijuana, the differences observed, while mostly very small in effect size (<.2), are consistent with at least some medical users employing marijuana to relieve symptoms and distress associated with medical illness. (Am J Addict 2015;XX:1–8)